Preparation and temperature-dependent photoluminescence properties of ScF3:Eu3+ submicroparticles. (10th July 2017) - Xu, Hualan; Liu, Ran; Xu, Bo; Li, Xinwei; Ouyang, Chuying; Zhong, Shengliang
Abstract : Negative thermal expansion Eu 3+ -doped ScF3 submicroparticles were prepared via a facile solvothermal method and their temperature-dependent luminescence properties were investigated. Abstract : In this study, negative thermal expansion (NTE) ScF3 submicroparticles were prepared and selected as host material. Various Eu 3+ concentrations (0.05–50%) in the doped ScF3 particles were obtained and their temperature-dependent photoluminescence (PL) properties were studied. The phase confirmation and morphology of the as-prepared ScF3 particles were investigated by X-ray powder diffraction (XRD) and scanning electron microscopy (SEM). The XRD results reveal that when the doping concentration reaches 3%, the EuF3 phase begins to form. The size of the ScF3 cubic particles ranges from 300 nm to 800 nm. The ScF3 :Eu 3+ (1%) submicroparticles were prepared and their PL properties were evaluated. The temperature-dependent luminescence results reveal that the luminescence intensity increases with the decrease in temperature in the range from 80 K to 450 K. Moreover, the decay time increases with a decrease in temperature. The crystal structure, electronic properties, dielectric functions, and absorption spectra have been systematically investigated for the Eu 3+ -doped ScF3 . First principles calculations were used to support and explain our experimental observations.